2015
DOI: 10.4236/oju.2015.56013
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Autosomal Dominant Polycystic Kidney Disease and Renal Cell Carcinoma

Abstract: Objectives: The relationship between autosomal dominant polycystic kidney disease (ADPKD) and renal cell carcinoma (RCC) is investigated to determine a link that would guide management due to elevated RCC risk. Current literature is inconclusive on this topic. Methods: This study is a retrospective chart review of patients having undergone nephrectomy. Those with pathology and history consistent with ADPKD were reviewed for presence of RCC. Results: The review at this institution revealed RCC in 18% of ADPKD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Nevertheless, some still consider ADPKD to be a risk factor for RCC. 7 The declining clinical status postoperatively and the resulting euthanasia of the cat in this report was suspected to be due to TE disease. The authors consider the RCC found in the removed right native kidney and its surgical manipulation during nephrectomy to be the cause of hypercoagulability resulting in the subsequent TE disease, along with other contributing factors such as anemia and sepsis.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Nevertheless, some still consider ADPKD to be a risk factor for RCC. 7 The declining clinical status postoperatively and the resulting euthanasia of the cat in this report was suspected to be due to TE disease. The authors consider the RCC found in the removed right native kidney and its surgical manipulation during nephrectomy to be the cause of hypercoagulability resulting in the subsequent TE disease, along with other contributing factors such as anemia and sepsis.…”
Section: Discussionmentioning
confidence: 74%
“…Similarly, in people, autosomal dominant polycystic kidney disease (ADPKD) is a common inherited cystic kidney disease affecting approximately six million people worldwide and is a prominent cause of end-stage renal disease (ESRD). 6,7 Resembling PKD in cats, ADPKD is due to mutations of either PKD1 in 85% of cases or PKD2 in the remaining 15%. 6 It has been speculated that there is a link between ADPKD and RCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular genetic diagnosis for patients and family members is now available, a great asset in genetic counselling. Genetic mutations associated with ADPKD are as common as one per 1000, which means at least 100 times more prevalent than the incidence of renal cell carcinoma [6,7].…”
Section: Commentarymentioning
confidence: 99%